An improved typical meteorological year for solar energy simulations in Rarotonga, Cook Islands. Issue 5 (20th October 2022) - Anderson, Timothy
ABSTRACT: Many of the Pacific's small island-nations have traditionally used diesel generators in the operation of their electricity grids. That said, more recently there has been a move towards greater use of renewable energy sources for electricity, in particular solar energy. A challenge to this, however, is ensuring that there is appropriate typical meteorological year data to facilitate an understanding of the output from these systems (especially at utility scale). Although there are numerous typical meteorological year datasets for the Pacific island-nations many of these are based on satellite inferred data. In this study, a typical meteorological year was developed for the island of Rarotonga, Cook Islands, using ground-based measurements. When compared to an existing typical meteorological year derived from satellite data, it was found that the satellite significantly overpredicted global horizontal irradiation for much of the year. This over-prediction was found to be due, at least in part, to the satellite data not resolving the effect of water in the atmosphere, (clouds and rainfall) on the solar irradiation correctly. On this basis, it demonstrates that although typical meteorological year derived from satellite data are a useful starting point for energy simulations in the Pacific island-nations, there is a need to improve these datasets to support their transition to renewable electricity generation.